Overview of Self Leadership during the COVID-19 Pandemic - A A Ngurah Bagus Aristayudha; Ni Made Widyani; Vitalia Fina Carla Rettobjaan (International Journal of Social Science and Business, 2021)
During the current covid-19 crisis, Bali's economic growth in 2020 shows that economic conditions in Bali are not going well. It makes organizational/company leaders adapt new strategies to survive the pandemic crisis. The behavior of leaders during a crisis will shape their qualifications as a good leader or a bad leader. Therefore, leaders must integrate this problem through a different approach than before. The purpose of this study was to analyze the differences in Self Leadership in entrepreneurial organizations, entrepreneurial individuals, non-entrepreneurial organizations, and non-entrepreneurial individuals. This research was conducted in Financial Evolution Bali with its members as respondents. The number of samples in this study was 90 respondents and used the Cluster Sampling method. The analytical technique used in this study is a different test analysis technique. Based on the analysis, it can be seen that there are differences in Self Leadership between organizational entrepreneurs and individual entrepreneurs. There are differences in Self-Leadership between organizational non-entrepreneurs and individual non-entrepreneurs. There are differences in Self Leadership between entrepreneurial organizations and non-entrepreneurial organizations. There are differences in Self Leadership between individual entrepreneurs and non-individual entrepreneurs. These differences can occur due to various factors, including the mindset, responsibilities, and burdens of each group.